Painless injections: Helfer skin tap technique - Joanne Kieffer Helfer (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
As of 12/2020 I have had 34 years clinical experience as an ED RN and 20 years as a Family Nurse practitioner. I have routinely given routinely injections most work days. My goal is to share my experience to alleviate suffering at any level if possible.